Dose-dependent thalidomide induced bradycardia in young erythema nodosum leprosum patient - Thangaraju, Pugazhenthan (Indian J Pharmacol, 2019)
The distressing consequences of immunology in leprosy is the lepra reaction. Erythema nodosum leprosum(ENL) in special cases need to be managed with capsule thalidomide in varying doses. We report such a case of bradycardia in thalidomide dose dependent manner in a young ENL male.